Ara' al-Khubara' Tijāh Taṣawwurāt Ṭalabah al-Marḥalah al-Jāmi'iyyah li Ta'allum Mādatay al-Naḥw wa al-Ṣarf: Mushkilāt wa Hulūl - Kamal, Ahmad Wafi; Alosman, Abdulrahman (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2024)
The Arabic language plays an important role in the lives of Muslims. Learning it as a foreign language is the wish of Malaysian students in schools and universities, however they often encounter difficulties and obstacles in the process of learning Syntax and Morphology due to multiple factors, including the difference in linguistic phenomena between the Arabic language and the Malay language. This research aims to identify the difficulties of learning Syntax and Morphology, explore the negative factors affecting the learning process, and monitor the experts’ opinions regarding the process of learning it as two effective tools in facilitating it for students majoring in the Arabic language in Malaysia. The researchers adopted the descriptive analytical approach and they used a questionnaire tool to obtain the data, and then analyzed and evaluated them based on the experts’ opinion in the field. The researchers concluded with a set of results, the most important of which are: Most of the study sample faced difficulties in learning Syntax and Morphology, and they agreed that the lack of practice and application is one of the main reasons for their weakness in both subjects, and one of the best methods suggested by the experts is to reformulate teaching method by the teachers, hoping that it will form targeted to all those concerned with this topic. تلعب اللغة العربية دوراً مهمًّا في حياة المسلمين، ويعد تعلمها لغة أجنبية أمنية الطلاب الماليزيين في المدارس والجامعات، لكن غالبًا ما يصطدمون بصعوبات وعراقيل في عملية تعلم النحو والصرف لوجود عوائق متعددة، منها: اختلاف الظواهر اللغوية بين اللغة العربية واللغة الملايوية. هدَفَ هذا البحث إلى التعرف على صعوبات تعلم مادتي النحو والصرف، واستكشاف العوامل السلبية المؤثرة في عملية التعلم، ورصد آراء الخبراء تجاه عملية تعلمها بوصفهما أداتين فاعلتين في التسهيل على طلبة تخصص اللغة العربية في ماليزيا. اعتمد الباحثان المنهج الوصفي التحليلي وقاما باستخدام الاستبانة للحصول على استجابات طلبة تخصص اللغة العربية، ومن ثم تحليلها وتقييمها بناء على آراء الخبراء في المجال. وقد انتهى الباحثان إلى مجموعة من النتائج، من أهمها: أن أغلب عينة الدراسة قد واجهوا صعوبات في تعلم علمي النحو والصرف، كما اتفقوا على أن قلّة الممارسة والتطبيق هي من الأسباب الرئيسة لضعفهم في كلتا المادتين، ووجه الخبراء إلى تغيير طريقة التدريس من قبل المعلمين من خلال تعديل المقررات التعليمية المدرسية.